DESIGN AND LICENSING TRENDS OF THE GENERAL EDUCATIONAL PROGRAMS IN LATVIA - Mihailovs, Ivans Jānis; Krūmiņa, Aira Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The general education program designing and licensing trends in Latvia in the period from 2010 to 2014 are analyzed in the article. Based on the general education program licensing data, it found that there isn’t a trend to license author’s program in primary education, while the secondary level of education author's programs are designed and licensed more often. The fact that primary education is more licensed programs in mathematics, science and technology, but in general secondary education – the humanitarian and social direction of the program suggest a possible gap in primary and secondary education. At the same time it found that a quarter of all licensed educational programs is not implemented, which could be result of socio-economic and political change in society.